2018
DOI: 10.1007/s12571-018-0814-3
|View full text |Cite
|
Sign up to set email alerts
|

Key factors influencing food security of smallholder farmers in Tanzania and the role of cassava as a strategic crop

Abstract: Due to beneficial characteristics of cassava such as robustness and versatility for multiple uses, it can have a major role in contributing to local food security. The objective of this study was to find out whether and how the cultivation of cassava benefits smallholder farmers in the regions of Dodoma and Morogoro, Tanzania. In addition, the study assessed the main factors that support or threaten food security of smallholder farmer households in the survey region and analysed whether cassava cultivation cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
40
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(43 citation statements)
references
References 27 publications
1
40
1
1
Order By: Relevance
“…Millions of tropical households depend on cassava (Manihot esculenta Cranz) for food and economic security [1,2]. Farmers cultivate cassava for its starchy storage roots and utilize semi-woody stem cuttings as propagules to establish the next cropping cycle.…”
Section: Introductionmentioning
confidence: 99%
“…Millions of tropical households depend on cassava (Manihot esculenta Cranz) for food and economic security [1,2]. Farmers cultivate cassava for its starchy storage roots and utilize semi-woody stem cuttings as propagules to establish the next cropping cycle.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that cassava can contribute to enhancement of food security status of farming households (Muhammad-Lawal, Omotesho, & Oyedemi, 2013;Widyanti et al, 2014, Ibok, Idiong, Brown, Okon, & Okon, 2014Saediman, Limi, Rosmawaty, Arimbawa, & Indarsyih, 2016;Reincke et al, 2018). However, studies that particularly focus on food security of poor cassava-growing households are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Smallholder farmers provide over 70% of the food consumed in Sub-Saharan Africa. Hence, this category plays a decisive role in terms of facilitating food security on the local, national, and global levels [11,12]. For example, in Tanzania, agriculture accounts for 25% of gross domestic product and more than 80% of the workforce are employed in the sector [13].…”
Section: Introductionmentioning
confidence: 99%